AKAR-AKAR: MERUBAH “MINDSET” MASYARAKAT MENUJU DESA KEMAKMURAN HIJAU - Maharani, Arfinta; Ningrat, Lalu Asrul Hadi; Puspitha, Rosa; Tejowulan, Sri (Jurnal Wicara, 2024)
Village Community Empowerment Real Work Lecture (KKN PMD) is a community service program organized by universities. In KKN PMD activities in Akar-Akar Village, Bayan District, North Lombok Regency, students and field supervisors at Mataram University carried out various activities with a focus on changing the community's mindset and developing village potential. The aim of the KKN PMD is to increase village potential, especially in the fields of agriculture and animal husbandry. The four (4) main methods applied are: (1) counseling about the importance of recognizing village potential and how to utilize it optimally, (2) counseling about effective farming and livestock techniques on dry land, (3) training in making alternative animal feed (silage ) from agricultural waste, and (4) planting fruit seeds of high economic value to improve the economy and community welfare. The results of this activity show an increase in community knowledge and understanding of the village's potential and how to better manage it. Apart from that, there is also an increase in farmers' knowledge and skills regarding productive agriculture and animal husbandry on dry land through planting fruit plants with high economic value, increasing forage for livestock, and using agricultural waste as alternative animal feed to increase community economic resilience and preserve the land environment. dry. It is hoped that the results of this activity can help farmers maximize village potential and facilitate their activities in farming and raising livestock. Overall, this KKN PMD activity has succeeded in overcoming several problems in Akar-Akar village, especially in development in the fields of agriculture and animal husbandry.